2015
DOI: 10.1021/acs.jafc.5b00244
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Curcumin: From Mechanism to Biological Implications

Abstract: Curcumin is the main bioactive ingredient in turmeric extract and widely consumed as part of the spice mix curry or as dietary supplement. Turmeric has a long history of therapeutic application in traditional Asian medicine. Biomedical studies conducted in the past two decades have identified a large number of cellular targets and effects of curcumin. In vitro curcumin rapidly degrades in an autoxidative transformation to diverse chemical species, formation of which has only recently been appreciated. We discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
250
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(288 citation statements)
references
References 61 publications
11
250
0
5
Order By: Relevance
“…However, this compound is highly unstable and its bioavailability is very low. It is supposed that, like the degradation products of delphinidin, those of curcumin are also active (45). Experiments need to be performed to better understand the metabolism and degradation pathways of these polyphenols and determine their modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, this compound is highly unstable and its bioavailability is very low. It is supposed that, like the degradation products of delphinidin, those of curcumin are also active (45). Experiments need to be performed to better understand the metabolism and degradation pathways of these polyphenols and determine their modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is known to degrade spontaneously by autoxidation in culture medium. 40 Although the 24 hours of incubation was performed in the dark, the degradation of curcumin is still expected. 41 This makes it difficult to calculate the percentage of curcumin released from the fibers based on the concentrations calculated.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…It has been reported that curcumin solubility in aqueous buffer (pH= 5.0) was only 11 ng/mL (7). Curcumin in the form of commercially available curcuminoid mixture is presently under investigation in more than 100 clinical trials (8). Capsules containing curcumin as powder were administered to healthy volunteers (9) as well as to cancer patients (10) in a high dose of 4-12 g/day.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical instability of curcumin under alkaline pH is well documented. Schneider et al published a number of interesting papers in which the degradation of curcumin in aqueous buffer was studied (8). They also studied the degradation mechanism and identified the formed products.…”
Section: Introductionmentioning
confidence: 99%